Efecto del destore en el racimo de banano (Musa spp.) variedad gran Williams y su incidencia en la producción. - Bermello Giler, Daniel Rumaldo (2014)
In order to evaluate the effect of destore bunch of banana (Musa spp) William incidence large variety in production field research was carried using a completely randomized design with 4 treatments and 5 replications. The results indicate no statistical significance for varieties or for repetitions According to the Tukey test at 95% probability, treatment T3, destore two weeks I presented the highest average fruit weight with 30.61 klg, treatment I present the highest average value in the calibration of hands was 1 week treatment T2 with a value of 44.16, I showed weeks treatment 1 with an average value of 10.45 inches, the treatment with the average value over low wastage rate was 2 weeks T3 treatment, with a 16 value of 4.32%, the highest value of exportable fruit showed what treatment 2 week with 29.29 klg, the average ratio of the treatment showed 2 weeks with the 1.50 cases / cluster was the highest value observed with treatment 2 week revenue of $ 14 522.00 was obtained, a value which is the highest compared to an income of witness $ 14 035,00 and other treatments, and 3 weeks 1 week earned revenues of $ 14 311.06 and $ 14 035.90 respectively.